ANALISIS NILAI EKUITAS TERHADAP PURCHASE DECISION DI MEDIASI BRAND AWARENESS DAN BRAND SATISFACTION PADA PRODUK KOPI KAPAL API DI SURAKARTA - Edi Priyono; Rima Parawati Bala; Totok Susilo Pamuji Nugroho (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the effect of value equity on brand awareness of Kapal Api coffee products in Surakarta, mediated by brand awareness and brand satisfaction. The population in this research consists of consumers who have purchased Kapal Api coffee products, with a sample of 150 respondents. The findings prove that value equity has a significant effect on brand awareness, brand satisfaction, and purchase decisions of Kapal Api coffee consumers in Surakarta. Furthermore, both brand awareness and brand satisfaction have a significant effect on purchase decisions. In addition, brand awareness and brand satisfaction are able to mediate the relationship between value equity and purchase decisions of Kapal Api coffee consumers in Surakarta. Keywords: Nilai ekuitas, Brand Awareness, Brand Satisfaction and Purchase decision